L’intelligence des machines et l’esprit du capitalisme - Jean-Sébastien Vayre (Communication)
The trend toward big data has spawned the development of so-called “intelligent” machines within organizations. Economic actors use these technologies to make sense of data and automate some of their cognitive activities. The author examines the history of these machines in order to better understand how they encapsulate the representations of intelligence that have evolved in conjunction with the production system dynamics characteristic of Western societies. He argues that there is congruence between machine intelligence and the spirit of capitalism.